anonymous
  • anonymous
Please Help Me With This Problem, I Don't Quite Know How To Do It. . . What Is The Solution Of The System? Use Substitution. x=y-6 6x-3y=-9
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
replace x in the second equation by y - 3, and get an equation with y alone \[6(y-3)-3y=-9\]
anonymous
  • anonymous
then solve for y. don't forget the distributive law. \[6y-18-3y=-9\] \[3y-18=-9\] \[3y=9\] \[y=3\]
anonymous
  • anonymous
I Got 6y-18-3y=9. . Now What Can I Do ?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Ohhh. Okay. Thank You Sooo Much!
anonymous
  • anonymous
oops i made a mistake. it was y- 6 not y - 3
anonymous
  • anonymous
i goofed. \[6(y-6)-3y=-9\]
anonymous
  • anonymous
\[6y-36-3y=-9\] \[3y-36=-9\] \[3y=27\] \[y=9\]
anonymous
  • anonymous
now since \[x=y-6\] and we know \[y=27\] we get \[x=27-6=21\]
anonymous
  • anonymous
sorry about my typo
anonymous
  • anonymous
thank you, and no problem, thanks!♥
anonymous
  • anonymous
welcome
anonymous
  • anonymous
Wait. . But The Multiple Choice Says: A.(-2,-3) B.(-2-2.7) C.(-3,-2) D.(3,5) And 21 Isn't Either of those. . . .
anonymous
  • anonymous
let me check see if i made a mistake
anonymous
  • anonymous
Okay, And It Says To Eliminate, Not Substitute.
anonymous
  • anonymous
ok yes i made a mistake. i wrote \[y=9\] but then for some reason wrote \[x=27-6\] instead of \[x=9-6=3\]
anonymous
  • anonymous
my fault sorry. i do not know why i put y = 9 and then used y = 27 however, i am sticking with (3,9) and the check is easy: first equation x= y - 6 and 3 = 9 - 6 second equation is \[6x-3y=-9\] and \[6\times 3 - 3 \times 9 = 18-27=-9\]
anonymous
  • anonymous
so (3, 9) is right even if it is not one of the choices.
anonymous
  • anonymous
elimination: rewrite \[x=y-6\] as \[x-y=-6\] and put \[6x-3y=-9\] underneath so it looks like \[x-y=-6\] \[6x-3y=-9\]
anonymous
  • anonymous
if you want to eliminate the "y" multiply the top equation all the way across by -3 to get \[-3x+3y=18\] \[6x-3y=-9\]
anonymous
  • anonymous
that way when you add the "y"s will drop out to give \[3x=9\] and so \[x=3\]
anonymous
  • anonymous
dont forget to multiply EVERYTHING by the constant, otherwise you will not have the same equation.
anonymous
  • anonymous
now you know \[x=3\] you can substitute back to find y = 9. as before.
anonymous
  • anonymous
Thank You!! (=

Looking for something else?

Not the answer you are looking for? Search for more explanations.